Alcoholism Causes Alveolar Macrophage Zinc Deficiency and Immune Dysfunction - Mehta, Ashish J.; Yeligar, Samantha M.; Elon, Lisa; Brown, Lou Ann; Guidot, David M. (American journal of respiratory and critical care medicine, 2013)
Alcohol use disorders cause oxidative stress in the lower airways and increase susceptibility to pneumonia and lung injury. Currently, no therapeutic options exist to mitigate the pulmonary consequences of alcoholism. We recently determined in an animal model that alcohol ingestion impairs pulmonary zinc metabolism and causes alveolar macrophage immune dysfunction. The objective of this research is to determine the effects of alcoholism on zinc bioavailability and alveolar macrophage function in human subjects. We recruited otherwise healthy alcoholics (n = 17) and matched control subjects (n = 17) who underwent bronchoscopy for isolation of alveolar macrophages, which were analyzed for intracellular zinc, phagocytic function, and surface expression of granulocyte-macrophage colony-stimulating factor receptor; all three of these indices are decreased in experimental models. Alcoholic subjects had normal serum zinc, but significantly decreased alveolar macrophage intracellular zinc levels (adjusted means [SE], 718 [41] vs. 948 [25] RFU/cell; P < 0.0001); bacterial phagocytosis (adjusted means [SE], 1,027 [48] vs. 1,509 [76] RFU/cell; P < 0.0001); and expression of granulocyte-macrophage colony-stimulating factor receptor β subunit (adjusted means [SE], 1,471 [42] vs. 2,114 [35] RFU/cell; P < 0.0001]. Treating alveolar macrophages with zinc acetate and glutathione in vitro increased intracellular zinc levels and improved their phagocytic function. These novel clinical findings provide evidence that alcohol abuse is associated with significant zinc deficiency and immune dysfunction within the alveolar space and suggest that dietary supplementation with zinc and glutathione precursors could enhance airway innate immunity and decrease the risk for pneumonia or lung injury in these vulnerable individuals.